PENERAPAN MODEL EXPERIENTIAL LEARNING DALAM PEMBELAJARAN SHOLAT ANAK USIA DINI DI TK ASSABIL 2 - Nesa Fatha Dinillah; Mukh Nursikin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Prayer is the most important part of instilling Islamic religious education in early childhood. Prayer, the second pillar of Islam, plays a role in instilling spiritual values, disciplined behavior, and fostering children's religious character. Therefore, methods that are not only cognitive but also involve practical activities, such as experiential learning, which focuses on direct experience in learning to pray, are needed. This study aims to analyze and describe the application of the experiential learning model in developing religious and moral values ​​in TK Assabil 2. This study used a descriptive qualitative approach through observation and documentation techniques. The results indicate that the application of the experiential learning model is effective in early childhood learning. This model encourages children to actively participate in prayer practices, thus fostering understanding of prayer movements and recitations and integrating learning experiences with the development of religious character.